A comparison between gravimetric and in-situ spectroscopic methods to measure the sorption of CO₂in a biocompatible polymer - Duarte, Ana Rita C. (2005)
In situ ATR-IR spectroscopy was used to simultaneously measure the sorption and swelling of carbon dioxide at high pressures in a biocompatible acrylate copolymer poly(methylmethacrylate-co-ethylhexylacrylate-co-ethyleneglycoldimethacrylate), P(MMA–EHA–EGDMA). The ν3 band of CO2 dissolved in the polymer (at 2335 cm−1) was used to calculate the sorption data and the polymer swelling was determined by analyzing the changes in the absorbance of the ν(C O) band (at 1730 cm−1) of the polymer. Transmission spectroscopy in the near-IR region was also used to study the sorption of CO2 in the polymer using combinational and overtone bands. The experiments were carried out in a pressure range of 2.0–12.0MPa and in a temperature range of 27–40 ◦C. The data for CO2 sorption in this polymer obtained by in situ spectroscopic methods have been compared to the data obtained by the gravimetric technique.